The Spatiotemporal Dimension of the Social License to Operate: The Case of a Landfill Facility in Algeria - Baba, Sofiane; Hemissi, Omar; Berrahou, Zoubida; Traiki, Chouki (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
Although the spatiotemporal dimension of social license to operate (SLO) issues is underexplored, the collective memory of a local community and the territorial anchoring of tensions are important factors in the SLO trajectory. Through the qualitative study of a socio-environmental controversy related to the establishment of a landfill facility in Algeria, this research deepens our understanding of the spatiotemporal dimension of SLO and offers two main contributions. The first clarifies four types of relational legacies. The second theorizes two mechanisms through which these relational legacies influence the SLO process: the mobilization of collective memory and the reification of the territory.